the Parafiscality in the 1991 Colombian Constitution - Romero Molina, Cesar Augusto; Lanzziano Rizo, Carlos; García Correa, Lina María (DIXI, 2013)
Parafiscality is an important, current topic in the study of Public Finance and Tax Law worldwide. Colombia is no stranger to this situation; it is thus necessary to determine the treatment that this institution has had in our Constitutional Jurisprudence since the Constitution of 1991.